Crime and Cybersecurity as Advanced Persistent Threat: A Constant E-Commerce Challenges - Desamsetti, Harshith (American Journal of Trade and Policy, 2021)
This study examines e-commerce technology and company cyber security threats. Technology for e-commerce is garnering academic and business attention. The business community and consumers can now do what was previously impossible. But it also created concerns, including cyber security. This study examines social engineering, denial of service, malware, and personal data assaults. Global firms spend a lot on cybersecurity, which grows each year. Because attackers constantly look for new vulnerabilities in persons, companies, and technology, it seems complicated to solve the obstacle. This study analyzes social engineering, DDoS, malware, and personal data threats. Using new technology for e-commerce and cybersecurity is a never-ending game of cat and mouse. Reliable technology, staff, customer training, and good corporate and government policies and regulations mitigate hazards.